Reduction of social coverage for symptomatic slow-acting drugs for osteoarthritis: a disinvestment initiative in Argentina, 2015-2017 - Martín A. Urtasun; María Noble; Martín Cañás; Julián Bustin; Ricardo C. Mastai; Alejandro J. Regueiro (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
In April 2016, the National Institute of Social Services for Retirees and Pensioners discontinued its policy of 100% coverage for 159 drugs (the "social subsidy"), including symptomatic slow-acting drugs for osteoarthritis (SYSADOAs), due to insufficient evidence of significant clinical benefit. We evaluated the effect of this measure on the use of SYSADOAs as well as non-steroidal anti-inflammatory drugs (NSAIDs), which were unaffected by this policy change. We compared outpatient dispensations of SYSADOAs and NSAIDs from 2015 to 2017, measuring dispensed units, retail price, and out-of-pocket expenses for beneficiaries each month. After the change in coverage, there was a 61.6% total decrease in SYSADOA units dispensed, and a 63.4% decrease in the final sales price to the public, measured in constant values. Dispensation was not reoriented towards NSAIDs, which fell by 6.1%. The incidence of new treatments decreased (from 6.4 to 3.3 treatments per 1,000 beneficiaries per month), as did their continuity. Beneficiaries' out-of-pocket spending on SYSADOAs increased by 75.8% (at constant values). Disinvestment in interventions with questionable therapeutic value is an important tool in working toward the sustainability of health systems.